PENGARUH PROMOSI, LIVE STREAMING DAN CELEBRITY ENDOSER TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINTIFIC - Zulfa, Derina; Astini, Rina (Universitas Prof. Dr. Hazairin SH, 2025)
The skincare industry in Indonesia has grown rapidly along with the increasing use of social media and e-commerce as marketing channels. Skintific, a skincare brand active in Indonesian e-commerce, is one example of a company that leverages digital marketing strategies. This study aims to analyze the influence of promotion, Live streaming, and Celebrity Endorsers on purchasing decisions for Skintific products. This research employed a quantitative approach using a survey of 102 consumers in West Jakarta. Data were analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0. The results show that promotion has a positive and significant effect on purchasing decisions, Live streaming has a positive and significant effect, and Celebrity Endorsers have the strongest influence. The implication of this study is that skincare companies should optimize the combination of promotion, interactive Live streaming, and collaboration with credible Celebrity Endorsers to enhance consumer purchasing decisions.